Intensive Glycemic Treatment Mitigates Cardiovascular and Mortality Risk Associated With Cardiac Autonomic Neuropathy in Type 2 Diabetes - Huimin Zhou; Yiquan Huang; Peihan Xie; Shaozhao Zhang; Menghui Liu; Zhenyu Xiong; Rihua Huang; Xingfeng Xu; Miaohong Li; Ziwei Zhou; Wenjing Zhang; Junqi Zhong; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Hyperglycemia is one of the proposed risk factors for cardiac autonomic neuropathy (CAN). CAN is associated with increased cardiovascular and mortality risk. But it remains unclear whether cardiovascular and mortality risk associated with CAN is mitigated by intensive glycemic treatment. Methods and Results This secondary analysis included 7866 patients from the ACCORDION (Action to Control Cardiovascular Risk in Diabetes Follow‐On) study. CAN was defined using ECG‐derived measures. End points included primary outcome (composite of cardiovascular events) and total deaths. During a median follow‐up of 8.9 years, a total of 1341 cardiovascular events and 1364 all‐cause deaths were ascertained. Compared with standard treatment, intensive treatment reduced risk of primary outcome and total deaths among patients with CAN but not among those without CAN. Compared with absence of CAN, the presence of CAN was associated with increased risk of primary outcome and total deaths in the standard group but not in the intensive group. Significant interactions were found between CAN status and treatment arms on risk of primary outcome and total deaths. Incidence rates per 100 person‐years of primary outcome and total deaths were similar between patients without CAN and those with CAN undergoing intensive treatment. Conclusions Intensive glycemic treatment mitigates cardiovascular and mortality risk associated with CAN and may serve as an effective way in the management of CAN.